Evolution of long centromeres in fire ants. Issue 1 (December 2016) - Huang, Yu-Ching; Lee, Chih-Chi; Kao, Chia-Yi; Chang, Ni-Chen; Lin, Chung-Chi; Shoemaker, DeWayne; Wang, John
Abstract Background Centromeres are essential for accurate chromosome segregation, yet sequence conservation is low even among closely related species. Centromere drive predicts rapid turnover because some centromeric sequences may compete better than others during female meiosis. In addition to sequence composition, longer centromeres may have a transmission advantage. Results We report the first observations of extremely long centromeres, covering on average 34 % of the chromosomes, in the red imported fire antSolenopsis invicta . By comparison, cytological examination ofSolenopsis geminata revealed typical small centromeric constrictions. Bioinformatics and molecular analyses identifiedCenSol, the major centromeric satellite DNA repeat. We found thatCenSol sequences are very similar between the two species but theCenSol copy number inS. invicta is much greater than that inS. geminata . In addition, centromere expansion inS. invicta is not correlated with the duplication ofCenH3 . Comparative analyses revealed that several closely related fire ant species also possess long centromeres. Conclusions Our results are consistent with a model of simple runaway centromere expansion due to centromere drive. We suggest expanded centromeres may be more prevalent in hymenopteran insects, which use haplodiploid sex determination, than previously considered.